EP 15. Muscle ultrasound imaging increases diagnostic sensitivity and aids prognosis in amyotrophic lateral sclerosis. Issue 9 (September 2016) - Heiling, B.; Hammer, N.; Stubendorff, B.; Grimm, A.; Ringer, T.; Prell, T.; Gunkel, A.; Schenk, A.; Axer, H.; Witte, O.W.; Grosskreutz, J.
Abstract : Background: Muscle ultrasound has become an important tool in the diagnosis of amyotrophic lateral sclerosis (ALS), because it can access muscle groups non-invasively which are difficult or dangerous to explore using EMG (tongue, diaphragm, abdominal muscles etc.). Also, it accesses larger muscle areas, and can quantify atrophy and fasciculation in a short examination time. Its role in regular clinical use for diagnosis and prognosis needs to be explored in larger cohorts. Objective: The aim of the study was to retrospectively estimate the diagnostic and prognostic value of muscle ultrasound in ALS in relation to longitudinal clinical parameters. Methods: 3 year ultrasonography data (echo intensity and fasciculation) in 6 muscle groups of 180 ALS patients were related to the onset type, disease duration, ALSFRS-R, its progression rate, and milestones (spread, ventilation, PEG, wheelchair). 23 of these 180 patients were re-examined to monitor both clinical an ultrasonographic changes over time. Results: Early on in ALS we consistently observed a significant increase in echo intensity in muscles with relatively preserved strength. This observation was more pronounced in patients who later on had a more aggressive disease course. Fasciculations were reliably detected early in disease but obtained diagnostic value only in muscles above knee level. Correlation with total ALSFRS-R and disease progression were inconsistent, likely due to the focality of ultrasound measurements. Conclusion: Muscle ultrasound has an established diagnostic value in early ALS. In addition, it may aid prognostic stratification which is important for patients planning, inclusion into future clinical trials and the understanding of the underlying pathology in relation to the genetic background of the patients.